Eksistensi Perlindungan Paten Atas Vaksin Covid-19 - Tharifah, Adzhani; Sardjono, Agus (UI Scholars Hub, 2021)
The Covid-19 vaccine is expected to be a solution to return to normal life. However, the need for vaccines that are global in nature raises several questions in the community, especially regarding the existence of patent protection. For this reason, this paper will answer these questions by discussing the patentability of the Covid-19 vaccine as well as how to implement patent protection in the midst of a pandemic and public concerns about limited access to vaccines. The research method used in the writing of this thesis is normative juridical with a qualitative approach where the data comes from literature studies and interviews. Based on the author's research, the author came to the conclusion that the Covid-19 vaccine can obtain patent protection as long as a patent application has been submitted to the patent office in which the vaccine meets all the patentability requirements. Due to the absence of an international patent protection mechanism, patent applications must be filed in many countries to maximize the scope of patent protection areas.